2017
DOI: 10.1080/19336918.2017.1338233
|View full text |Cite
|
Sign up to set email alerts
|

Substrate rigidity-dependent positive feedback regulation between YAP and ROCK2

Abstract: Extracellular matrix (ECM) stiffness influences gene expression, leading to modulation of various cellular functions. While ROCK2 regulates actomyosin activity as well as cell migration and proliferation, expression of ROCK2 is increased in response to stiffening ECM. However, the mechanism underlying rigidity-dependent ROCK2 expression remains elusive. Here, we show that YAP, a mechanically regulated transcription coactivator, upregulates ROCK2 expression in an ECM rigidity-dependent manner. YAP interacted wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 41 publications
1
20
0
Order By: Relevance
“…We have demonstrated that expression of the gene encoding Rho-associated coiled coilcontaining protein kinase (ROCK) 2, which induces the activation of myosin II, is increased in response to the rigid substrate in a YAP-TEAD dependent manner [9]. On the other hand, nuclear accumulation of YAP, in turn, depends on ROCK2 expression, as shown previously [10] and in Figure 3A. Therefore, we wondered whether ROCK2 played a role in the expression of MMP24 in cells cultured on the rigid substrate.…”
Section: Resultssupporting
confidence: 70%
See 4 more Smart Citations
“…We have demonstrated that expression of the gene encoding Rho-associated coiled coilcontaining protein kinase (ROCK) 2, which induces the activation of myosin II, is increased in response to the rigid substrate in a YAP-TEAD dependent manner [9]. On the other hand, nuclear accumulation of YAP, in turn, depends on ROCK2 expression, as shown previously [10] and in Figure 3A. Therefore, we wondered whether ROCK2 played a role in the expression of MMP24 in cells cultured on the rigid substrate.…”
Section: Resultssupporting
confidence: 70%
“…Similarly, the expression levels of two YAP target genes, CTGF and MMP7, were also elevated in cells grown on the rigid substrate ( Figure 1C and D). We have previously shown that rigid substrates promote YAPdependent transcription in MCF-7 cells [9,10]. We therefore examined whether YAP regulated MMP24 expression.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations